X-ray sources population in NGC 1559 - Nurnabilah Nazri; Adlyka Annuar (Penerbit Universiti Kebangsaan Malaysia, 2020)
We present Chandra observation of the nearby spiral galaxy NGC 1559 to study the X-ray sources population in the galaxy. Based on our analysis, we detect twenty-four X-ray sources in the galaxy, of which six have 0.5–8 keV luminosities exceeding 1039 erg s-1, suggesting that they are possibly ultra-luminous X-ray source (ULX) candidates. The remaining eighteen sources have 0.5–8 keV luminosities below this threshold value, suggesting that they are likely to be X-ray binary candidates. We perform X-ray spectral analysis for the six ULX candidates and found that in general, their properties are broadly consistent with that found for other ULXs. The number of X-ray sources found in this galaxy is relatively high as compared to other galaxies with similar star formation rate of ~2.8 M- yr-1. This however could be attributed to the relatively high number of supernova occurrence (four) in the galaxy observed in the past years. We did not detect any X-ray nuclear point source in the galaxy, suggesting that NGC 1559 does not host an active galactic nucleus. This is supported by its HII optical spectral classification and our infrared analysis using WISE.